Occupational chloracne : report by the Industrial Injuries Advisory Council in accordance with Section 171 of the Social Security Administration Act 1992 considering prescription for occupational chloracne.: report by the Industrial Injuries Advisory Council in accordance with Section 171 of the Social Security Administration Act 1992 considering prescription for occupational chloracne. ([2013]) - Great Britain., Industrial Injuries Advisory Council,
No abstract available